History and National Integration: A Study of Collective Memory of Tamiang Monuments in Medan 1894 - Rahman, Aulia; Ibrahim, Husaini; Prasetyo, Okhaifi; Usman, Usman; Riyani, Mufti (Diponegoro University, 2024)
This paper focuses on the historical exploration and collective memory of the Tamiang Monument in Medan, Indonesia. This paper examines how monuments can build collective memory and link history to people's lives at a certain time so that it can be interpreted. Through historical methods, the study results show that the Tamiang Monument plays an essential role in the inheritance of collective memory about the conquest of Tamiang as part of the Aceh region by the Dutch colonialists. The monument is an important symbol to remind people of the greatness and courage in the struggle against the colonizers. However, after the Tamiang Monument was destroyed, all narratives and reminders of the Tamiang War were lost. The loss of this monument also has implications for the loss of the values of the legacy of tenacity, fighting spirit, and collective identity associated with this important event. Therefore, it is important to rebuild the Tamiang Monument as an initial step to revive collective memory and pass on the values of struggle to the younger generation. Monuments play an important role in building and maintaining the community's collective identity and strengthening the historical awareness of the Tamiang and Aceh communities.